2021
DOI: 10.1021/acsearthspacechem.1c00082
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Forms of Mercury in Pilot Whales Determined from Species-Averaged Mercury Isotope Signatures

Abstract: Marine mammals detoxify organic methylmercury (MeHg) as inorganic mercury selenide (HgSe), yet the nature of the reaction intermediate species and the tissue-specific redistribution of Hg species in the body are unknown. We report that the identity and proportion of the dominant Hg species in long-finned pilot whale (Globicephala melas) tissues can be obtained from the bulk variation of isotopic values of δ 202 Hg against the extent of demethylation (percentage of total Hg as MeHg, %MeHg) using an alternating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(44 citation statements)
references
References 45 publications
(176 reference statements)
1
43
0
Order By: Relevance
“…This interpretation conflicts with two recent Hg isotope studies performed on 22 petrel tissues from 8 individuals and 89 whale tissues from 28 individuals [4,15]. The δ 202 Hg value of a tissue (δ 202 Hgt) is the weighted sum of the MDF of each Hg species (Spi) expressed as follows:…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…This interpretation conflicts with two recent Hg isotope studies performed on 22 petrel tissues from 8 individuals and 89 whale tissues from 28 individuals [4,15]. The δ 202 Hg value of a tissue (δ 202 Hgt) is the weighted sum of the MDF of each Hg species (Spi) expressed as follows:…”
mentioning
confidence: 80%
“…They concluded that the δ 202 Hg values of the HgSe nanoparticles from each tissue of individual petrels are specific to the HgSe species alone and that the Hg(Sec)4 → HgSe reaction occurs without fractionation of the 202 Hg isotope. We show (1) that the HgSe nanoparticles are mixtures of MeHgCys, Hg(Sec)4, and HgSe, and therefore that the δ 202 Hg values are not species-specific, and (2) that the 202 Hg isotope is actually fractionated during the Hg(Sec)4 → HgSe reaction, and therefore that this isotope can be used to trace the Hg metabolic pathways between tissues in a single individual and in different animals.It was shown recently that the Clark's grebe, giant petrels, long-finned pilot whales, and blue marlins detoxify the organic methylmercury cysteinate (MeHgCys) complex by the stepwise MeHgCys → Hg(Sec)4 → Hgx(Se,Sec)y → HgSe demethylation reaction [2][3][4][5]. Hg(Sec)4 is a fourcoordinate selenocysteine complex and HgSe is tiemannite.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“… 36 , 70 73 , 83 The MeHg endmember has relatively uniform δ 202 Hg values across tissues, likely explained by the efficient exchange of MeHg between blood and tissues throughout the body. 70 , 71 , 73 …”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%